AIDS : een multidisciplinaire aanpak - Baro, F.; Branckaerts, J.; Desmyter, J. (Leuven : Federatie van Consultatiebureaus voor Levens- en Gezinsvragen, 1987)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie